2022
DOI: 10.3390/ijms23063377
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogen-Induced MATE Gene TaPIMA1 Is Required for Defense Responses to Rhizoctonia cerealis in Wheat

Abstract: The sharp eyespot, mainly caused by the soil-borne fungus Rhizoctonia cerealis, is a devastating disease endangering production of wheat (Triticum aestivum). Multi-Antimicrobial Extrusion (MATE) family genes are widely distributed in plant species, but little is known about MATE functions in wheat disease resistance. In this study, we identified TaPIMA1, a pathogen-induced MATE gene in wheat, from RNA-seq data. TaPIMA1 expression was induced by Rhizoctonia cerealis and was higher in sharp eyespot-resistant whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…To evaluate the effect of MeJA treatment on Dn1, we first examined the expression levels of TaPIEP1 (pathogen-induced ERF encoding gene) and TaPIMA1 (pathogen-induced MATE) genes, which were previously reported to be the marker genes in response to JA ( Dong et al., 2010 ; Su et al., 2022 ). The results showed that at 5°C and -10°C, the expression of TaPIEP1 and TaPIMA1 in the MeJA treatment group was significantly higher than that in the control group ( Figure 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the effect of MeJA treatment on Dn1, we first examined the expression levels of TaPIEP1 (pathogen-induced ERF encoding gene) and TaPIMA1 (pathogen-induced MATE) genes, which were previously reported to be the marker genes in response to JA ( Dong et al., 2010 ; Su et al., 2022 ). The results showed that at 5°C and -10°C, the expression of TaPIEP1 and TaPIMA1 in the MeJA treatment group was significantly higher than that in the control group ( Figure 1A, B ).…”
Section: Resultsmentioning
confidence: 99%
“…However, unlike EDS5, in A. thaliana EDS5H is constitutively expressed in green tissues independent of pathogen infection and does not contribute to pathogen-induced SA accumulation (Parinthawong et al ., 2015). Nevertheless, MATE proteins transport a broad range of, such as organic acids, plant hormones, and secondary metabolites, which could influence QDR (Nawrath et al ., 2002; Takanashi, et al ., 2014; Su, et al ., 2022). Conversely, BBX18, as well as the additional XK1 and FBA1 genes in the potential deletion linked to resistance, lack documented defense associations.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, we utilized the FDR to manage the expected proportion of false positives among significant associations. FDR values for both GEM and GWA were determined using the q value R package (Storey 2011 ). Bonferroni thresholds for GWA and GEM are 6.64 and 6.03-Log 10 P, respectively, ( P < 0.05) and 6.34 and 5.73 −Log 10 P ( P < 0.1).…”
Section: Methodsmentioning
confidence: 99%